2020
DOI: 10.1002/jbio.201960200
|View full text |Cite
|
Sign up to set email alerts
|

Miniature probe for dual‐modality photoacoustic microscopy and white‐light microscopy for image guidance: A prototype toward an endoscope

Abstract: In this study, a novel photoacoustic microscopy (PAM) probe integrating white‐light microscopy (WLM) modality that provides guidance for PAM imaging and complementary information is implemented. One single core of an imaging fiber bundle is employed to deliver a pulsed laser for photoacoustic excitation for PAM mode, which provides high resolution with deep penetration. Meanwhile, for WLM mode, the imaging fiber bundle is used to transmit two‐dimensional superficial images. Lateral resolution of 7.2 μm for PAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…To further utilize the scalability of PAM, quad mode system was developed which used dual element focused circular array transducers, focused irradiation, and diffused irradiation to provide four combinations of resolution and depth in a single system (Liu et al, 2018). Scope of applications of PAM has also been expanded by using it in conjugation with other imaging modalities like OCT (Chang et al, 2019), surgical microscope (Lee et al, 2015), ultrasound imaging (Rebling et al, 2018), 2-photon microscopy (Soliman et al, 2015;Song et al, 2016), fluorescence microscopy (Yan et al, 2017;Zhang et al, 2018b;Shemetov et al, 2020), diffuse optical tomography (Yang et al, 2013), and white light microscopy (Li et al, 2020a). These studies further demonstrate that multi-modal imaging techniques can provide more information without making the imaging systems too bulky or cumbersome to use, and thus use of such systems seems more favourable in the future.…”
Section: Photoacoustic Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…To further utilize the scalability of PAM, quad mode system was developed which used dual element focused circular array transducers, focused irradiation, and diffused irradiation to provide four combinations of resolution and depth in a single system (Liu et al, 2018). Scope of applications of PAM has also been expanded by using it in conjugation with other imaging modalities like OCT (Chang et al, 2019), surgical microscope (Lee et al, 2015), ultrasound imaging (Rebling et al, 2018), 2-photon microscopy (Soliman et al, 2015;Song et al, 2016), fluorescence microscopy (Yan et al, 2017;Zhang et al, 2018b;Shemetov et al, 2020), diffuse optical tomography (Yang et al, 2013), and white light microscopy (Li et al, 2020a). These studies further demonstrate that multi-modal imaging techniques can provide more information without making the imaging systems too bulky or cumbersome to use, and thus use of such systems seems more favourable in the future.…”
Section: Photoacoustic Microscopymentioning
confidence: 99%
“…A highly sensitive optoacoustic detector was designed using a side-looking focused ultrasound transducer with an integrated miniature preamplifier circuit to increase the SNR. Now, research is moving towards integrating PAE with other imaging modalities such as white-light endoscopy (WLE) (Li et al, 2020a) for image guidance. Li et al (Li et al, 2020a) reported a novel design to combine PAM and white-light microscopy (WLM) in a miniature probe of 1.7 mm in diameter.…”
Section: Photoacoustic Endoscopymentioning
confidence: 99%
“…In addition to EUS, pure optical imaging modalities such as optical coherence tomography (OCT), [79][80][81] hyperspectral imaging (HSI), [75] fluorescence imaging (FI) [78,82] and white-light imaging (WLI) [83] have also been combined with PAE for complementary derivation of tissue properties. In 2013, Jiang et al presented a dualmodality image probe combining optical-resolution photoacoustic microscopy (ORPAM) and OCT. [74] As shown in Figure 7B, the laser beams emitted from a pulsed laser and super luminescent diode (SLD) are coupled into a single- mode fiber, and then focused by a miniature GRIN lens.…”
Section: Photoacoustic-optical Endoscopymentioning
confidence: 99%
“…Various thickness extension mode (TEM) pMUTs have been developed and applied in endoscopic PAI based on different piezoelectric materials, including PVDF [ 60 , 61 , 62 ], LiNbO 3 [ 40 , 63 , 64 , 65 , 66 ], PZT [ 24 , 41 , 43 , 46 , 67 , 68 , 69 ], and PMN-PT [ 70 , 71 , 72 ]. Progress has been made in reducing pMUT size, improving pMUT sensitivity, and achieving high-resolution PAI by using different piezoelectric materials and fabricating high-frequency pMUTs and focused pMUTs.…”
Section: Pmuts and Their Endoscopic Pai Applicationsmentioning
confidence: 99%
“…The same group developed catheters for intravascular photoacoustic imaging with diameters of 1.1 mm and 0.9 mm [ 41 , 42 ]. Moreover, Li et al integrated photoacoustic microscopy and white-light microscopy into a 1.7 mm diameter miniature probe for image guidance, where the same 40 MHz pMUT from Blatek was employed [ 67 ]. In this work, by coupling two lasers (wavelength of 532 nm and 680 nm) into one single core of the imaging bundle, scalable lateral resolution and imaging depth were also achieved.…”
Section: Pmuts and Their Endoscopic Pai Applicationsmentioning
confidence: 99%